Effects of sinomenine on the expression of microRNA-155 in 2,4,6-trinitrobenzenesulfonic acid-induced colitis in mice. - Qiao Yu (Public Library of Science (PLoS), 2013)
Background Sinomenine, a pure alkaloid isolated in Chinese medicine from the root of Sinomenium acutum, has been demonstrated to have anti-inflammatory and immunosuppressive effects. MicroRNAs (miRNAs) are gradually being recognized as critical mediators of disease pathogenesis via coordinated regulation of molecular effector pathways. Methodology/findings After colitis was induced in mice by instillation of 5% (w/v) 2,4,6-trinitrobenzenesulfonic acid (TNBS), sinomenine at a dose of 100 or 200 mg/kg was orally administered once daily for 7 days. We evaluated body weight, survival rate, diarrhea score, histological score and myeloperoxidase (MPO) activity. The mRNA and protein expression levels of miR-155, c-Maf, TNF-α and IFN-γ were determined by quantitative RT-PCR and immunohistochemistry, respectively. Sinomenine (100 or 200 mg/kg)-treated mice with TNBS-induced colitis were significantly improved in terms of body weight, survival rate, diarrhea score, histological score and MPO activity compared with untreated mice. Both dosages of sinomenine significantly decreased the mRNA and protein expression levels of c-Maf, TNF-α and IFN-γ, which elevated in TNBS-induced colitis. Furthermore, sinomenine at a dose of 200 mg/kg significantly decreased the level of miR-155 expression by 71% (p = 0.025) compared with untreated TNBS-induced colitis in mice. Conclusions/significance Our study evaluated the effects and potential mechanisms of sinomenine in the anti-inflammatory response via miRNA-155 in mice with TNBS-induced colitis. Our findings suggest that sinomenine has anti-inflammatory effects on TNBS-induced colitis by down-regulating the levels of miR-155 and several related inflammatory cytokines.